Genetic and Transcriptomic Variation Linked to Neutrophil Granulocyte–Macrophage Colony-Stimulating Factor Signaling in Pediatric Crohn's Disease. Issue 3 (13th August 2018) - Denson, Lee A; Jurickova, Ingrid; Karns, Rebekah; Shaw, Kelly A; Cutler, David J; Okou, David; Valencia, C Alexander; Dodd, Anne; Mondal, Kajari; Aronow, Bruce J; Haberman, Yael; Linn, Aaron; et al.
Abstract: Background: Granulocyte–macrophage colony-stimulating factor auto-antibodies (GMAbs) suppress neutrophil-extrinsic GM-CSF signaling and increase risk for stricturing behavior in Crohn's disease (CD). We aimed to define clinical, genomic, and functional associations with neutrophil-intrinsic GM-CSF signaling. Methods: Missense mutations in CSF2RA, CSF2RB, JAK2, STAT5A, and STAT5B were identified using whole-exome sequencing in 543 pediatric inflammatory bowel disease (IBD) patients. Neutrophil-intrinsic GM-CSF signaling was defined using the GM-CSF-induced STAT5 stimulation index (GMSI) in 180 pediatric IBD patients and 26 non-IBD controls. Reduced GM-CSF signaling (GMSI-Lo) was defined as the 20th percentile within the control group. Variation in neutrophil phospho-protein abundance, bacterial killing, and the global pattern of gene expression with the GMSI was determined. Results: We validated 18 potentially damaging missense mutations in CSF2RA and CSF2RB . CSF2RA A17G carriage increased from 10% in those with intact neutrophil GMSI to 32% in those with low GMSI ( P = 0.02). The frequency of reduced Staphylococcus aureus killing increased from 17% in those with intact neutrophil GMSI to 35% in GMSI-Lo neutrophils ( P = 0.043). Crohn's disease neutrophils with low GMSI exhibited specific alterations in phospho-protein networks and genes regulating cytokine production, wound healing, and cell survival and proliferation. Stricturing behavior increased from 7% in patients with both low GMAb and intact GMSI to 64% in patients with both elevated GMAb and low GMSI ( P < 0.0001). Conclusions: Low/normal neutrophil-intrinsic GM-CSF signaling is associated with CSF2RA missense mutations, alterations in gene expression networks, and higher rates of disease complications in pediatric CD.